2019
DOI: 10.21272/jnep.11(3).03009
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Phase Formation Features of Ti-Zr-Ni Quasicrystalline Films under Heating

Abstract: The paper describes the growth features of thin Ti-Zr-Ni films prepared by the method of magnetron sputtering of the targets with compositions Ti53Zr30Ni18 and Ti41Zr38.3Ni20.7 on the substrates at 300 K with subsequent annealing in vacuum. The formation peculiarities of phase composition, structure and thermal stability of quasicrystalline thin films were studied. It was established that in initial state the films were X-ray-amorphous or nanocrystalline with coherence lengths (according to Scherrer) near 1.6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The film thickness ranged from 20 nm to 14.6 m. A detailed description of the method for preparing films is given in [7]. The elemental composition of the targets and films was controlled by X-ray fluorescence analysis [9].…”
Section: Objects and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The film thickness ranged from 20 nm to 14.6 m. A detailed description of the method for preparing films is given in [7]. The elemental composition of the targets and films was controlled by X-ray fluorescence analysis [9].…”
Section: Objects and Methodsmentioning
confidence: 99%
“…In addition, the film-target saturated with tritium can be used as an important device of the neutron source generator based on the D-T reaction [5]. There are few works devoted to the formation of quasicrystalline coatings of the Ti-Zr-Ni system [5][6][7], in contrast to the Al-Cu-Fe system [8]. When deposited on a "cold" substrate, as a rule, the coating is always amorphous, and when deposited on a substrate heated to 500-700 C, it is difficult to maintain the required composition [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed characterization of the structure of the films we obtained in the initial state was given in [5]. There, the peculiarities of the formation of their structure and phase composition were discussed, and the temperature boundaries of the stability of the quasicrystalline phase in thin films were determined under vacuum annealing for 1 h. It was found that the quasicrystalline phase is formed in the temperature range of 500 to 550 C.…”
Section: Characterization Of the Initial Statementioning
confidence: 99%
“…In the Ti-Zr-Ni system, the formation of a quasicrystalline icosahedral phase in a 100 μm thick surface layer was first observed upon pulsed irradiation of a massive Ti41.5Zr41.5Ni17 alloy with flows of hydrogen, helium, or argon with thermal loads up to 0.6 MJ/m 2 in [4]. The features of the formation of a quasicrystalline thin-film coating are described in [5,6].…”
Section: Introductionmentioning
confidence: 99%